Anomalous asymmetry of fusiform and parahippocampal gyrus gray matter in schizophrenia: A postmortem study. - McDonald, B; Highley, JR; Walker, M; Herron, B; Cooper, S; Esiri, M; Crow, T (2000)
OBJECTIVE: Anomalies of structure and asymmetry of the parahippocampal gyrus (origin of the perforant path input to the hippocampal formation in the medial temporal lobe) have been shown in some postmortem studies of schizophrenia, but previous studies have not included the fusiform gyrus (which may have a role in facial recognition and naming), adjacent to the parahippocampal gyrus on the ventral occipitotemporal surface. METHOD: The volumes of gray matter in the left and right parahippocampal and fusiform gyri were assessed with a stereological point-counting technique in the temporal lobes from formalin-fixed brains of 27 comparison subjects and 31 patients with schizophrenia. Age was a covariate and gender was a factor in the analysis. RESULTS: In relation to the comparison subjects, the schizophrenic patients (both sexes) had lower volumes of both the parahippocampal and fusiform gyri on the left side. For both structures a left-greater-than-right volume asymmetry was present in the comparison subjects, but this asymmetry was reversed in the parahippocampal and fusiform gyri of the schizophrenic patients. A sex difference was present with respect to age at onset-degree of anomaly of asymmetry for both gyri increased with age at onset in men but not in women. CONCLUSIONS: The findings add substance to the view that the sex-related dimension of symmetry/asymmetry is integral to the disease process in schizophrenia and draw attention to the fusiform gyrus as a structure of particular interest in relation to disturbances of identification and naming in psychosis.